"I Am My Home": Aged Out Foster Youth's Discursive Constructions of Home. Issue 2 (15th March 2022) - Nelson, Leslie R.; Thomas, Lindsey J.
Abstract : The present study explores how aged out foster youth discursively construct home in light of their experiences before, during, and/or after aging out of foster care. Results from 30 interviews with aged out foster youth revealed three primary themes represented participants' sensemaking around home: home as a place (where), home as family, and home as self. The current study offers unique theoretical and practical implications for researchers and professionals who work with foster youth during their transition out of care. Limitations and directions for future research are presented.